Penerapan Akuntansi Manajemen Dalam Pengambilan Keputusan Bisnis - Nurwidia, Lusiana; Purwanti, Purwanti (GLOBAL SCIENTS PUBLISHER, 2025)
Management accounting is one of the key tools utilized by companies to support the business decision-making process. This study aims to assess the implementation of management accounting in facilitating business decisions within organizations. Using a descriptive qualitative approach, the research explores how financial and non-financial information generated by management accounting systems can be leveraged to formulate strategies, control costs, and enhance operational efficiency. The findings reveal that management accounting plays a significant role in strategic decisions, such as pricing, resource allocation, and performance evaluation. By providing reliable and timely data, management accounting enables managers to make more data-driven and logical decisions. This study recommends enhancing the integration between management accounting and the business decision-making process to strengthen the company's competitiveness in a dynamic market environment..